Closing chapters : urban change, religious reform, and the decline of Youngstown's Catholic elementary schools, 1960-2006 - Welsh, Thomas G., 1961- (Lexington Books, 2011)
Closing Chapters attempts to explain the disintegration of urban parochial schools in Youngstown, Ohio, a onetime industrial center that lost all but one of its eighteen Catholic parochial elementary schools between 1960 and 2006. Through the examination of Youngstown, Welsh sheds light on a significant national phenomenon: the fragmentation of American Catholic identity.